Sosialisasi dan Demontrasi Pengolahan Sampah Sebagai Bahan Pengembangan Kreatifitas Anak Berbasis Lingkungan di Yayasan Al-Kahfi, Medan - Lubis, Desy Irana Dewi; Azizah Mutiara; Lubis, Delima Fitriani; Waruwu, Depi Hasrat; Siburian, Novika (Welfare : Jurnal Pengabdian Masyarakat, 2023)
The purpose of this activity is to increase the knowledge, skills, and understanding of the children at the orphanage foundation about the importance of disposing of trash properly and reprocessing waste into items that can be reused. To carry out this activity, the demonstration method will be used. Demonstration is a method of presenting lessons by demonstrating to students a particular process, situation, or object, either real or just an imitation. The participants consisted of 30 children of primary and junior high school age. From this community service activity, it can be interpreted that the knowledge and understanding of the children in the orphanage have increased, and their skills and creativity have also developed, so that they have skills from an early age.